Complex assemblages, complex social structures: rural settlements in the upper and middle Thames Valley 100BC to AD100 - Morrison, W (Cambridge Scholars Publishing, 2015)
Late Iron Age and Early Roman Britain has often been homogenised by models that focus on the resistance/assimilation dichotomy during the period of transition. Complex Assemblages examines the rural settlements of this period through the lens of Cultural Theory in order to tease out the more nuanced and diverse human landscape that the material suggests. This approach develops new ways of thinking about the variability observed in rural settlements from the end of the Middle Iron Age (MIA) to the early 2nd century AD; the selected study area is the Upper and Middle Thames Valley. This book uses the grid/group designations of Mary Douglas’ Cultural Theory as a tool to produce a more multifaceted picture of the period, exploring the assemblages of these rural settlements to understand the nature of the socio-political structures of the region, beyond the anonymity of tribal affiliation and the faceless economic dichotomy of high and low status.